APIKASI MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max) PADA TANAH GAMBUT INDRAGIRI HILIR - Yoyon Riono. (Jurnal Agro Indragiri, 2019)
This study aims to study the effect of composition of doses of chicken manure and rice husk ash on the growth and production of soybean (Glycine max) on peat soils. This research was conducted in the month of February 2013 to June 2013 in the Tembilahan Hulu Village, Tembilahan Hulu District, Indragiri Hilir Regency. Initial soil analysis was carried out at the BPTP Yogyakarta Laboratory. This study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications and 3 replications, namely without treatment and treatment of chicken manure doses in the same 3 treatments namely 2500 kg / ha, for rice husk ash using 500 kg / ha, 1000 kg / ha and 1500 kg / ha, so that the combination can be repeated in 3 replications so that there are 12 experimental units, each experimental unit consists of 10 plant pots. The parameters observed were soil chemical properties, plant height, number of effective root nodules (100%), percentage of pithed pods, number of seeds / plants, weight of 100 seeds (grams). The data can be analyzed statistically, if the F count is greater than the F table followed by the Tukey HSD test at the 5% level. The results showed that the combination of chicken manure and rice husk ash was significantly different from plant height and weight of 100 seeds. In the parameters of the number of effective root nodules (100%), the percentage of effective root nodules, the percentage of pithed pods, the dry weight of seeds / plants, showed no significant effect. The best weight of 100 soybean seeds is found in the combination dose of 2500 kg chicken / ha chicken manure and 1000 kg / ha of rice husk ash which is 16.20 g.